Exercise Addiction and Personality: a Two-Decade Systematic Review of the Empirical Literature (1995–2016) (Baltic Journal of Sport and Health Sciences, 2017)
Background. It is largely unknown why among millions of exercisers a small proportion become addicted to the behaviour in a similar manner to other common addictions, such as alcohol addiction. Some scholars believe that specific personality characteristics may be involved in predisposing some individuals to exercise addiction. Method. The objective of the current paper was to systematically review papers concerning exercise addiction over a two-decade period (1995–2016) and to establish the extent to which personality factors are related to the aetiology of exercise addiction. Results. The results demonstrated that perfectionism and narcissism are associated with exercise addiction and that the association is stronger in the presence of obsessive-compulsiveness. It was also found that other factors (e.g., anger, hostility, anxiety, depression, and dysfunctional psychological regulation) appear to be associated with exercise addiction. In relation to the Big Five personality traits, it was found that exercise addiction could not be unequivocally associated with openness, extroversion, neuroticism, and conscientiousness. Furthermore, the diverse focus, methodologies, and samples on which the empirical research base relies make it difficult to develop a model accounting for the role of personality factors in exercise addiction. Conclusion.  The  conclusion  that  can  be  drawn  is  that  personality  factors  are  clearly  involved  in  exercise addiction, but the extent to which they exert their effects in the many different situations and stages of addiction requires further research using more robust methods and representative samples.Keywords:  athletes, exercise addiction, exercise dependence, physical activity, training, compulsive exercise,  obligatory exercise, personality traits.